2021
DOI: 10.3390/agronomy11122377
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry WRKY Transcription Factor WRKY50 Is Required for Resistance to Necrotrophic Fungal Pathogen Botrytis cinerea

Abstract: WRKY protein is one of the largest plant-specific transcription factors that plays critical roles in plant stress responses, but few WRKY transcription factors have been functionally analyzed in strawberry. In this study, a Botrytis cinerea response WRKY gene, FvWRKY50, was isolated from the woodland strawberry. Expression analysis indicated that the transcript of FvWRKY50 was gradually decreased with fruit ripening, but was significantly induced by B. cinerea infection in mature strawberry fruit. Subcellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…( Supplementary Table S9 ). One of the significant plant-specific transcription factors is encoded by the WRKY gene family, discovered in several plant species ( Ma et al., 2021 ) which have highly expressed genes. A team of researchers from the Louisiana State University ( Fountain et al., 2015 ) reported similar results in maize with respect to the resistance and susceptibility to A. flavus fungal infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Supplementary Table S9 ). One of the significant plant-specific transcription factors is encoded by the WRKY gene family, discovered in several plant species ( Ma et al., 2021 ) which have highly expressed genes. A team of researchers from the Louisiana State University ( Fountain et al., 2015 ) reported similar results in maize with respect to the resistance and susceptibility to A. flavus fungal infection.…”
Section: Discussionmentioning
confidence: 99%
“…WRKY plays a vital role in biotic stress and is involved in PAMP signaling and multiple defense responses through mitogen-activated protein kinase (MAPK) signaling, especially in sensing pathogen effectors or PAMP, and also interacts with resistance (R) protein ( Meng and Zhang, 2013 ). Numerous studies have shown that a significant proportion of WRKY TFs are involved in disease response via the jasmonic acid (JA) signaling pathway ( Ma et al., 2021 ). These TFs act as repressors or activators of basal defense responses ( Windram et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have proposed a crucial role of WRKY in plant defense ( Eulgem and Somssich, 2007 ; Amorim et al, 2017 ; Wani et al, 2021 ). Examples of WRKY that play roles in pathogen resistance response include Triticum aestivum WRKY19 in the defense against Puccinia striiformis , Fragaria × ananassa WRKY50 in the defense against Botrytis cinerea , Oryza sativa WRKY6 in the defense against Xanthomonas oryzae , and Hordeum vulgare WRKY6 in the defense against Pyrenophora teres ( Ma et al, 2021 ; Tamang et al, 2021 ; Im et al, 2022 ; Nobori, 2022 ). Cucumber contains 61 WRKY that are classified into 3 main groups (I, II, and III) ( Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Strawberry WRKY11 influences the expression of other TFs such as WRKY1, WRKY70, and MYB1, and then positively regulates plant resistance to B. cinerea [51]. Other WRKY transcription factors including WRKY10 in cucumber and grapevine [15], WRKY25 [52] and WRKY50 [53] in strawberry, WRKY31 [54] and WRKY46 in tomato [55], and rose WRKY41 [56] were also reported to improve resistance to B. cinerea, while Lily WRKY39 and WRKY41a [57] have negative roles in plant resistance to B. cinerea. In addition, rose WRKY13 promoted resistance to B. cinerea by enhancing cytokinin content and reducing abscisic acid signaling [58].…”
Section: Wrky Transcription Factorsmentioning
confidence: 99%